Us Before Me - Illingworth, P. author. aut Link
XX, 264 p.
Keywords: Patricia Illingworth's short, powerful and passionate book argues that "social capital" should be an essential ethical concept guiding our actions, and explains how one might go about implementing this idea in a positive way.